2020
DOI: 10.1101/2020.03.09.984625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Object representations in the human brain reflect the co-occurrence statistics of vision and language

Abstract: A central regularity of visual perception is the co-occurrence of objects in the natural environment. Here we use machine learning and fMRI to test the hypothesis that object cooccurrence statistics are encoded in the human visual system and elicited by the perception of individual objects. We identified low-dimensional representations that capture the latent statistical structure of object co-occurrence in real-world scenes, and we mapped these statistical representations onto voxelwise fMRI responses during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
4
1
Order By: Relevance
“…Our model is also not intended to explain the effects of navigational experience on the PPA, which shows stronger responses to objects that occur at navigationally important locations and treats stimuli as more similar if they come from the same place (14, 15, 48). Furthermore, our findings do not account for functional differences along the anterior-posterior extent of the PPA, which appear to reflect a general trend toward visual-form representations in the posterior PPA and mnemonic representations in the anterior PPA (31, 49, 50). However, future studies could leverage our mid-level modeling framework to test whether the effects of navigational experience in the PPA involve the modulation of mid-level features from navigationally important stimuli and to test whether the mnemonic representations of anterior PPA are implemented through the associative coding of mid-level features from co-occurring stimuli, including object categories in scenes and distinct views of places (14, 31).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Our model is also not intended to explain the effects of navigational experience on the PPA, which shows stronger responses to objects that occur at navigationally important locations and treats stimuli as more similar if they come from the same place (14, 15, 48). Furthermore, our findings do not account for functional differences along the anterior-posterior extent of the PPA, which appear to reflect a general trend toward visual-form representations in the posterior PPA and mnemonic representations in the anterior PPA (31, 49, 50). However, future studies could leverage our mid-level modeling framework to test whether the effects of navigational experience in the PPA involve the modulation of mid-level features from navigationally important stimuli and to test whether the mnemonic representations of anterior PPA are implemented through the associative coding of mid-level features from co-occurring stimuli, including object categories in scenes and distinct views of places (14, 31).…”
Section: Discussioncontrasting
confidence: 85%
“…We next performed a stringent test of how well our encoding models could generalize to new data by examining their ability to predict the average responses of the PPA in a separate fMRI dataset with different subjects and novel stimuli. We examined data from an fMRI study of object representation in which four subjects viewed images of isolated objects from 81 different categories (31). We found that our encoding models trained on the BOLD5000 dataset were highly accurate at predicting the fMRI responses of the PPA to novel stimuli in a completely different set of subjects (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work suggests that PPA represents scenes and landmarks [71][72][73][74] but also represents associations between objects driven by spatial and temporal contiguities. [75][76][77] A recent study identified a grouping effect in right PPA and the hippocampus for objects in different rooms using a passive viewing task similar to the one we use here, 78 and other studies have identified grouping effects in hippocampus for items that are experienced together in time. 35 We suspect that grouping effects would have been stronger in the current study if we had not controlled for visual co-occurrence across segments by making all objects co-visible and controlled for temporal proximity by constraining the order in which objects were searched for during learning.…”
Section: Articlementioning
confidence: 53%